Upregulated plasma and urinary levels of nucleosides as biological markers in the diagnosis of primary gallbladder cancer1. Issue 21 (22nd September 2014) - Jiao, Xingyuan; Mo, Yuxuan; Wu, Ying; He, Jinyun; Zhang, Peng; Hu, Ronglin; Luo, Canqiao; Du, Jun; Fu, Jian; Shi, Jinsen; Zhou, Liansuo; Li, Dongming
<x xml:space="preserve">Abstract</x> We first detected aberrant nucleoside levels in the plasma, urine, bile, and tissues from cases and controls to explore them as biomarkers in the diagnosis of gallbladder cancer. Reversed‐phase high‐performance liquid chromatography was used to assess the levels of ten nucleosides in these samples from gallbladder cancer patients, gallstone patients, and healthy controls. Plasma and urine samples were collected from patients with gallbladder cancer (n = 202), patients with gallstones (n = 203), and healthy controls (n = 205); bile and tissue samples were collected from 91 gallbladder cancer patients, 93 gallstone patients; and 90 were donated after cardiac death. Of the ten nucleosides analyzed, eight urinary nucleosides, five plasma nucleosides, three bile nucleosides, and one tissue nucleoside were significantly upregulated in the gallbladder cancer patients compared to control groups (p < 0.05). Among these upregulated nucleosides, the sensitivity, specificity, and accuracy of urinary nucleosides in the diagnosis of gallbladder cancer patients were 89.4, 97.1, and 95.7%, respectively, those of plasma nucleosides were 91.2, 95.6, and 94.2%, respectively, those of bile nucleosides were 95.3, 96.4, and 95.1%, respectively, and those of tissue nucleosides were 86.2, 93.8, and 92.6%, respectively. These results suggest that nucleosides may be as useful as biological markers for gallbladder cancer.